ABDOMINAL MUSCLE LDH IN MICE DURING IMMUNOSTIMULATION AND INDUCED HEPATITIS B - V. VIVEKA VARDHANI; P. J. R. NATHANAEL; G. SAKUNTHALA (The Bioscan, 2011)
Lactate dehydrogenase (LDH) content in the biological systems is indispensably concerned with the tissue breakdown and cytotoxicity during various aliments. The prime objective in recent medical advances is to conceptualize the degree of cytotoxicity mainly in human diseases. The present work is centralized on the impact of Immunex DS on male Swiss albino mice innoculated with various doses of Gene Vac B vaccine. Six groups of male Swiss albino mice were immunostimulated by Immunex DS and innoculated with various single doses of Gene Vac B vaccine containing HbsAg, and compared the intense tissue break down and cytotoxicity in their abdominal muscles. The present findings clearly confirm elevated level of LDH which correlates with the extent of tissue break down and cell death during induced hepatitis B induction.